Integrating Gresik’s local cultural wisdom into character education for shaping the Pancasila student profile - Anis, Fahimatul; Nugroho, Prasetyo Adi; Hutami, Trapsila siwi; Puspitaningrum, Dyah Ayu; Nasution; Katsuhisa , Shirai (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This study investigates the possibility of incorporating Gresik local cultural wisdom into character education lessons to achieve the Pancasila student profile. This research technique uses a qualitative research approach. Data collection includes limiting study scope, acquiring information by observation and formal and informal interviews, and documenting findings. The aggregation of open-ended data, derived from common questions, and information processing from many participants are essential elements of data analysis. The cultural knowledge of the Gresik people will be the primary subject of this investigation. More particularly, the discussion topics will be pasar bandeng, rebo wekasan, festival damar kurung, sanggring, and macanan. According to the research findings and the language that describes it, character education in Gresik's local cultural wisdom contains the values of teamwork, patriotism, diligence, creativity, and religious character. This research highlights the innovative aspects of the diverse local wisdom values found in Gresik. Educational institutions can use these values as educational tools to cultivate the character traits outlined in the Pancasila student profile